Impact of red blood cell transfusion dose density on progression-free survival in patients with lower-risk myelodysplastic syndromes - de Swart, Louise; Crouch, Simon; Hoeks, Marlijn; Smith, Alex; Langemeijer, Saskia; Fenaux, Pierre; Symeonidis, Argiris; Cermâk, Jaroslav; Hellström-Lindberg, Eva; Stauder, Reinhard; Sanz, Guillermo; Mittelman, Moshe; et al. (Haematologica, 2020)
Progression-free survival (PFS) of patients with lower-risk myelodysplastic syndromes (MDS) treated with red blood cell transfusions is usually reduced, but it is unclear whether transfusion dose density is an independent prognostic factor. The European MDS Registry collects prospective data at 6-monthly intervals from newly diagnosed lower-risk myelodysplastic syndromes patients in 16 European countries and Israel. Data on the transfusion dose density - the cumulative dose received at the end of each interval divided by the time since the beginning of the interval in which the first transfusion was received - were analyzed using proportional hazards regression with time-varying co-variates, with death and progression to higher-risk MDS/acute myeloid leukemia as events. Of the 1,267 patients included in the analyses, 317 died without progression; in 162 patients the disease had progressed. PFS was significantly associated with age, EQ-5D index, baseline World Health Organization classification, bone marrow blast count, cytogenetic risk category, number of cytopenias, and country. Transfusion dose density was inversely associated with PFS (P<1×10-4): dose density had an increasing effect on hazard until a dose density of 3 units/16 weeks. The transfusion dose density effect continued to increase beyond 8 units/16 weeks after correction for the impact of treatment with erythropoiesis-stimulating agents, lenalidomide and/or iron chelators. In conclusion, the negative effect of transfusion treatment on PFS already occurs at transfusion densities below 3 units/16 weeks. This indicates that transfusion dependency, even at relatively low dose densities, may be considered as an indicator of inferior PFS. This trial was registered at www.clinicaltrials.gov as #NCT00600860.
Keywords: myelodysplastické syndromy; Erythrocyte Transfusion; Izrael; Progression-Free Survival; Myelodysplastic Syndromes; Humans; Israel; prospektivní studie; lidé; Europe; Evropa; transfuze erytrocytů; doba přežití bez progrese choroby; Prospective Studies